Implementasi Multimedia CD Interaktif Untuk Meningkatkan Aktivitas Dan Hasil Belajar Tema 6 Kelas II SDN Merjosari 04 Kota Malang - Sugiharto, Firsta Bagus; Mirayanti, Mirayanti; Iten, Feronika (Jurnal PGSD: Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2022)
The aims of this research are a) To increase student learning activities in learning theme 6 caring for animals and plants, sub theme 6 learning 4 class 2 SDN Merjosari 04 Malang City and b) To improve student learning outcomes. The subjects of this study were all 2nd grade students totaling 28 children. Teaching media that can support the ongoing learning activities are interactive multimedia CD. This research is classroom action research (CAR) which was carried out in two cycles, each cycle consisting of one meeting. The cycle consists of four stages of research, namely planning, implementation, observation and reflection. The implementation of this research is successful if at least 75% of students get a score of 70. The results of the implementation of this research are: (1) The average score of student learning activities in the first cycle is 6.0 in the medium category, and the average score student activity in the second cycle is 10.9 with a high category. while (2) the mastery of student learning outcomes classically in the implementation of the first cycle, namely 78.57% of students who scored above 70 and in the implementation of the second cycle 96.43% of students scored above 70.